Pressure‐Induced Metallic Conductivity in the Single‐Component Molecular Crystal [Ni(dmit)2] (Eur. J. Inorg. Chem. 24/2014). Issue 24 (August 2014) - Cui, Hengbo; Tsumuraya, Takao; Miyazaki, Tsuyoshi; Okano, Yoshinori; Kato, Reizo
Abstract : The back cover picture shows a diamond anvil cell and a mounted sample in the cell, which is the setup used for measuring the electrical conductivity of a small single‐component molecular crystal of a metal–dithiolene complex, [Ni(dmit)2 ], under very high pressure (up to 25.8 GPa). The pressure is comparable to the lower mantle pressure (more than 600 km deep in the earth). This very high pressure changes the insulating crystal to a metal with a three‐dimensional Fermi surface. Details are discussed in the Short Communication by H. Cui, R. Kato et al. onp. 3837 ff .